2019
DOI: 10.7554/elife.48186
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent deterioration of nuclear pore assembly in mitotic cells decreases transport dynamics

Abstract: Nuclear transport is facilitated by the Nuclear Pore Complex (NPC) and is essential for life in eukaryotes. The NPC is a long-lived and exceptionally large structure. We asked whether NPC quality control is compromised in aging mitotic cells. Our images of single yeast cells during aging, show that the abundance of several NPC components and NPC assembly factors decreases. Additionally, the single-cell life histories reveal that cells that better maintain those components are longer lived. The presence of hern… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 86 publications
11
84
1
Order By: Relevance
“…However, a recent study performed in yeast concluded that oxidative damage is unlikely to be a direct cause for the age‐dependent deterioration of nuclear transport. Alternatively, Rempel et al (2019) proposed that in aged cells, misassembled NPCs accumulate as a result of NPC assembly quality control decline leading to a reduction of permeable and functional NPCs, and a consequent decrease in the transport dynamics (Rempel et al, 2019).…”
Section: Nuclear Transportmentioning
confidence: 99%
“…However, a recent study performed in yeast concluded that oxidative damage is unlikely to be a direct cause for the age‐dependent deterioration of nuclear transport. Alternatively, Rempel et al (2019) proposed that in aged cells, misassembled NPCs accumulate as a result of NPC assembly quality control decline leading to a reduction of permeable and functional NPCs, and a consequent decrease in the transport dynamics (Rempel et al, 2019).…”
Section: Nuclear Transportmentioning
confidence: 99%
“…In dividing cells, NPCs disassemble during mitosis and rearrange afterwards in the newly formed cells (180). Rempel et al showed that NPC quality control is compromised in aging mitotic cells, which results in decreased NPC function and impaired transcription factor shuttling (181). The maintenance of NPCs in long-lived post-mitotic cells, such as neurons, is provided through the renewal of individual NPC subcomplexes, whereby scaffold Nups remain assembled and installed in the NPC during the entire cellular life span (144,182).…”
Section: Nct Impairments In Normal Agingmentioning
confidence: 99%
“…The assembly of new NPCs is complex and heavily dependent on the presence of the proper amounts of NPC components and assembly factors. Altogether, the biochemical properties of NPCs set them at risk for age‐related decline and, indeed, several studies addressed age‐related changes of the NPC, and/or nucleocytoplasmic transport in aging .…”
Section: Introductionmentioning
confidence: 99%